Electronic Access to Agronomy Journals: A Follow-up Study. - Brad Brazzeal (Issues in Science and Technology Librarianship, 2015)
User studies of faculty, staff, and students in research universities have shown a strong preference and even an expectation for electronic access to journals. In 200: the author and a colleague examined the electronic availability of 47 agronomy journals at eight libraries that had Association of Research Libraries (ARL) membership and that also served institutions with doctoral programs in agronomy. In late 201: the author replicated the study to determine the extent to which electronic access to those journals at the same institutions had changed over time. While there was a clear increase in electronic availability, much of the content was still not available online. [ABSTRACT FROM AUTHOR]